The legal protection of human rights sceptical essays - Campbell, Tom, 1938-; Ewing, K. D. (Keith D.); Tomkins, Adam. (Oxford : Oxford University Press, 2011)
The value and legitimacy of using courts to limit the powers of governments in the domain of human rights is a significant ongoing debate. This book provides a critical review that explores the alternative means for protecting and promoting human rights.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human rights -- Congresses; Law